Postmaterialism and postmodernization in Australian electoral politics - Charnock, David; Ellis, Peter (Elsevier, 2004)
In this paper we explore recent Australian electoral politics using both Inglehart’s ideas on postmaterialism and also a broader conception of postmodern attitudes. We begin by demonstrating that the widely-used postmaterialism measure based on Inglehart’s four-item question gives completely counterintuitive results for the most recent significant Australian party, the One Nation Party. This appears to support Warwick’s argument that this measure actually reveals pro-democracy propensity. Subsequently, we develop a much broader measure of postmodern attitudes and use this in conjunction with an index of left-right attitudes to explore the positioning of party supporters in the resulting two-dimensional space and the practical consequences of this. Among other things, this demonstrates that a single left-right dimension is inadequate to describe the positioning of minor parties in particular, but that it is overall of more significance in predicting vote than is the postmodern dimension.